The Effect of Training, Education, and Knowledge on Improving Tax Consultant Performance Karya Artha Bhakti Group - Linggi, Erik Amba; Mangetan, Larissa; Bangkaran, Natasya; Roreng, Petrus Peleng; Beloan, Bertha (Tangible Journal, 2024)
The Effect of Training, Education, and Knowledge on Improving the Performance of Karya Artha Bhakti Group Tax Consultants. This study aims to determine the effect of training, education, and knowledge on employee performance at Karya Artha Bhakti Group. The independent variables are training (X1), education (X2), and knowledge (X3), and the dependent variable is employee performance (Y). The population is made up of all 31 employees of Karya Artha Bhakti Group. The sampling technique is saturated sampling; data collection is done using questionnaires, and validity and reliability tests are carried out. The data analysis techniques employed in this study include descriptive analysis, data normality tests, f tests, and t tests. This study found that training has a positive and significant effect on employee performance. Education as a positive and significant effect on employee performance, and knowledge has a positive and significant effect on employee performance, so all hypotheses are accepted. Companies should continue to increase their investment in employee training and education.